Human Capabilities for Fair Development: Case Study of Women Prawn Farmers in Dipasena, Lampung - Gadis Arivia (Jurnal Perempuan, 2017)
This study examines the role of women prawn farmers in Dipasena, East Rawajitu District, Tulang Bawang, Lampung and what it means for human development in Indonesia. Several focus group discussions and indepth interviews with women prawn farmers and fishermen community were conducted to collect data and understand comprehensively the issues that women prawn farmers face in a patriarchal culture where they are not acknowledged as women workers. This paper uses a feminist perspective on women and work and Martha Nussbaum’s capability categories. This paper concludes that women’s roles and contribution in fishery and in national development is not recognized and not accommodated in national and local policies. Women’s role in fishery industry is considered non-existent in this society and therefore restrict their potential and meaningful existence and respect on equal human dignity.